Unexpected - kampung / Mohd Hamidi Adha Mohd Amin - Mohd Amin, Mohd Hamidi Adha (Faculty of Art and Design, 2021)
UNEXPECTED-KAMPUNG consists of a randomized pattern that derives from ONE IMAGE (village house). Based on this one image, the artist uses various android design applications which produce unexpected patterns. The creation of this pattern is variable based on elements that are available on the ONE IMAGE. These unexpected pattern outcomes are beautiful yet interesting to look for. The artist wants to show the audience that there are secrets within the one image. To extract these patterns, we need to explore and explore until we find the pattern that satisfies us. As we can see through the artwork, unexpected geometric lines that appear which increase the aesthetic shock to the artist itself. Moreover, on One image, you will notice, there are various visuals that you recognize, which are stone walls, elements of nature and wood. These elements, when correctly combined, will produce beautiful yet unexpected patterns.